Peningkatan Technical Skill, Pengembangan SDM dan Problem Solving Pada Toko SS - Ramadhi Ramadhi; Nora Damayanti; Edo Andrefson; Kiki Sarianti; Yolanda Desti; Desi Rosalina (Universitas 45 Surabaya, 2023)
In the era of globalization, traditional retail stores face increasingly complex challenges, especially with the emergence of technology and changes in consumer behavior. One important aspect that traditional retail shop owners need to pay attention to is technical skills, human resource development and problem solving which aims to improve technical skills in the context of traditional retail shops which is the focus of this research. As technology advances, physical retail stores must understand and integrate various aspects of technology to ensure smooth operations and remain competitive in an ever-changing marketplace. SS Stores require increased technical skills, human resource development and problem solving in running their business. The method in this activity uses the Participatory Action Research (PAR) method which aims to determine the systematic process or steps used as a means to achieve certain goals effectively. The importance of developing technical skills, managing human resources (HR), and problem solving abilities is the key to success, therefore every retail business is certainly obliged to improve technical skills, develop human resources and solve problems in business.